Realizing the personality traits of Bisha University Employees during the Covid-19 pandemic (Journal Of Educational and Psychological Researches, 2022)
The post-Corona Covid-19 world is not the world before it, the problem of perception of personality traits with two axes: the characteristics of psychological and social compatibility, and the second aspect the mental disorder during the pandemic, and the accompanying precautions and prohibitions during the academic year 2020 AD. The aim of the research is to reveal the perception of the personal characteristics of Bisha University employees (students and faculty) during the Corona Covid-19 pandemic, and to reveal statistically significant differences in the perception of the personality traits of Bisha’s members during the Covid 19 according to the scientific qualification variables (female students -faculty members),  marital status (bachelor , married), by using the Personality Perception Questionnaire (prepared by the researcher and its standard characteristics were verified). It has been applied it to a random sample of (94) employees of the University of Bisha. The results of the research concluded that the university’s employees enjoy psychological and social compatibility and the absence of symptoms of psychological disorder despite the existence of the pandemic and the lockdown. There are no statistically significant differences at the level of (0.05) in the perception of personality traits according to the scientific qualification variable and the social status variable.